EXPLORING THE MOTIVATIONS BEHIND INTENTIONAL USE OF TIKTOK SHOP FOR HOTEL RESERVATIONS - Kumaradewi M, Ni Putu Dhanan (Bajang Institute, 2025)
The utilization of TikTok has evolved beyond its original function as a social media platform to serve as a digital commerce, including for hotel reservations. While existing studies have explored various factors influencing consumer purchasing behavior on TikTok, a limited research specifically examines the roles of celebrity endorsement, emotional marketing, and brand image in shaping consumers’ intentions to purchase service-based offerings, such as hotel bookings. This study aims to investigate the factors influencing Generation Z’s purchase intention when booking hotels via TikTok Shop. Using a quantitative approach, data were collected from 125 respondents aged 21 to 25 years in Bali, all of whom had previously made a hotel reservationat one time through TikTok. The analysis using Smart-PLS 3.0 showed that celebrity endorsement, emotional marketing, and brand image significantly impact purchase intention. These findings support the Theory of Planned Behavior (TPB). Practically, they offer strategic insights for the hospitality sector, advising companies to: (1) partner with influencers matching their target audience's traits, (2) create emotionally engaging content such as storytelling and testimonials, and (3) maintain a positive and cohesive brand image across all platforms